KAITAN HUKUM ISLAM DENGAN PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - U., M. Sabir (Institut Agama Islam Negeri (IAIN) Palu, 2007)
During the prophetâs life, all legal problemsÂ would be returned to him. Then, he wouldÂ make a decisionÂ on those problems. It is different from Â our contemporary era since the prophet has passed awayÂ while there areÂ some problems brought about by the development of science and of technology. For example, Â transplantation and insemination, both of which should be discussed by Muslim scholars to determineÂ Â whether or not both are permitted by Islam. IfÂ both are banned or are permitted, then whatÂ are the conditions for banningÂ orÂ permitting them. Within this context, this article elaborates the relationship between Islamic law and the development of science and of technology.Kata Kunci : hukum Islam, ilmu pengetahuan, teknologi